On Reducible Degeneration of Hyperelliptic Curves and Soliton Solutions - Nakayashiki, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2019)
In this paper, we consider a reducible degeneration of a hyperelliptic curve of genus g. Using the Sato Grassmannian, we show that the limits of hyperelliptic solutions of the KP hierarchy exist and become soliton solutions of various types. We recover some results of Abenda, who studied regular soliton solutions corresponding to a reducible rational curve obtained as a degeneration of a hyperelliptic curve. We study singular soliton solutions as well and clarify how the singularity structure of solutions is reflected in the matrices that determine soliton solutions.